Resposta de Euschistus heros (Hemiptera: Pentatomidae) a extratos de soja de diferentes cultivares. - SILVA, José Victor da; PRADO, Deyvid Martins do; SALMAZZO, Gustavo Ruivo; ZAZYCKI, Luiza Cristiane Fialho (ANAIS DO ENIC, 2022)
-